Primary stroke prevention in China – a new approach. (20th May 2015) - Feigin, Valery L.; Wang, Wenzhi; Fu, Hua; Liu, Liping; Krishnamurthi, Rita; Bhattacharjee, Rohit; Parmar, Priya; Hussein, Tasleem; Barker-Collo, Suzanne
Abstract : The growing burden of stroke in China, along with the increasing cost of health care calls for new, more effective strategies for stroke prevention. These strategies should include increasing awareness of stroke symptoms, awareness of risk factors, and provision of easily available information on means of modifying risk factors. The Stroke Riskometer App is exactly such a tool, available in Mandarin, for adult individuals to calculate their risk of stroke over the next 5 and 10 years, and to identify their individual stroke risk factors and linking them to possible means of modifying these risk factors. The use of this App could reduce the risk of stroke for individuals in the Chinese population and contribute to significant reduction in stroke burden in China.